Optimalisasi Pemanfaatan Lahan Permukiman Melalui Pemodelan Konsolidasi Lahan Menggunakan Citra Quickbird: Studi Di Desa Caturtunggal, Kecamatan Depok, DIY - WIDYANINGRUM, Ade Ayu ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The research was conducted in Caturtunggal village, Depok Subdistrict, Sleman District. The design of land consolidation in this study using remote sensing technology and geographic information systems. The purpose of this study are to optimize the modeling of land consolidation and to review the accuracy of QuickBird imagery in providing spatial data to construct of urban land consolidation model. The method used in this study are a combination amongst visual imagery interpretation, data processing using GIS, and field surveys. The land consolidation location is determined based on three variables: residential environmental quality, undeveloped land potential, and suitability of spatial use. residential environmental quality are determined by layout parameters, density, size, types of building, road availability derived from imagery interpretation and sanitary conditions derived from field work. The land consolidation design performed by the method of land area approach. The design of land consolidation is used by structuring land persil. Restructuring isbased on the principle of proximity with the previous location and itis all organized have direct access to the road. The result shows that Quickbird imagery is able to use as data source parameters in order to determine the location of the land consolidation priority. Meanwhile, for more detailed land mapping needs more research. The accurate result of interpretation reached 86.36% in the land use interpretation, for the residential layout reached 83.33%, 88.89% for building densit, 88.89% for building size, and 83.33% for the building type. The mapping location of land consolidation is divided into five priority classes. At first priority class or the most prioritized for land consolidation has an area of 87.97 hectares or 8.83 % of the area of the Caturtunggal village. The second priority class has an area of 183.07 ha (18.38 %), the third priority class has an area of 39.73 ha (3.98 %), the fourth priority class has an area of 306.44 ha (30.76 %), and the fifth priority class has an area of 379.05 Ha (38.05 %). At selected locations as an example design of land consolidation consists of 19 blocks and 122 plots building. Key words: Quickbird Imagery, Geographic Information System, Land Consolidation.